RELATIONS OF TWO AUTHORITARIAN REGIMES: SPAIN AND CHILE DURING THE GOVERNMENTS OF PRIMO DE RIVERA AND IBÁÑEZ DEL CAMPO. - Carrellán Ruiz, Juan Luis (Revista de Historia Social y de las Mentalidades, 2024)
This work wants to emphasize the importance of the diplomatic and economic relations, which took place during Primo de Rivera and Ibáñez del Campo mandates, between Spain and Chile. For that purpose, there has been analyzed the diplomatic existing documentation in different Spanish and Chilean Archives. It also reflects the opinions written on the Spanish press about the politics designed by Colonel Carlos Ibanez. These relations were based on the ideological sympathy of both regimes which propitiated very intense connections in different areas, such the political and diplomatic areas with the arbitration agreement signature and the elevation to the maximum level of both legations, those of military character with the Chilean officials training in Spanish training centres, and those of commercial sign with two agreements, the reduction of duties and the internment of saltpetre in Spanish territory